Synthesis of ferroelectric BaTi2O5 nanoparticles via modifying peroxopolytitanic acid solution - Yamada, Katsumi; Miyazaki, Hidetoshi; Tsukada, Shinya (Ceramics international, 2020)
A peroxopolytitanic acid (Ti-IPA) solution was prepared through a direction reaction of H2O2/NH3 and metallic titanium powder. A BaTi2O5 precursor powder was prepared by a reaction of the prepared Ti-IPA and a Ba(OH)2 aqueous solution. The obtained BaTi2O5 precursor powders were heat treated at 1000 °C for 10 h; the resulting BaTi2O5 was almost single phase with a particle size of approximately 200–600 nm. The Raman scattering spectra for the BaTi2O5 powders were measured at various temperatures, and the full width at half maximum (FWHM) was evaluated in low-frequency quasi-elastic scattering. From the temperature dependence of the FWHM results, the transition temperature of the resulting BaTi2O5 was 460 ± 10 °C.